Typography, Morphology, and Syntax Characteristics of Texting - Haryono Haryono; Bambang Lelono; Asrofin Nur Kholifah (Bina Nusantara University, 2018)
The main purpose of this research was to investigate Indonesian, English, and Japanese linguistic characteristics of Short Text Messages (SMS) performed by students. In particular, this research tried to seek linguistic characteristics in terms of typography, morphology, and syntax. Furthermore, the long term purpose of this research was to find out the difference of linguistic characteristics of those languages as well as its socio-pragmatic implication of the short text messages. This research applied content analysis for its method which made use of records or document as the main source of data in terms of recording, official records, text book, reference, letter, autobiography, pictures, movies, cartoon, etc. Meanwhile, technique of analysis included several stages such as defining text, categorizing text, verifying text category, assessing the accuracy of text coding, revising the criteria of text coding, reassessing the category of text coding, coding entire texts, and finally reassessing the accuracy of coding. The identical language characteristics between SMS used by the student to communicate with their lecturers and universal language charateristics are found in this research. The research expectedly provides the main resource for improvement of language learning that enables students to use language appropriately.